Leptomischus flaviflorus (Rubiaceae), a new species from India - Hareesh, Vadakkoot Sankaran; Wu, Lei; Sabu, Mamiyil (Phytotaxa, 2017)
Leptomischus flaviflorus, a new species from Arunachal Pradesh, India, is here described and illustrated. Detailed description, distribution, ecology, colour photographs, and key to identification for Leptomischus species are provided.